Relationship between Adding Value, Trust and Job Satisfaction Based on Teachersâ Perceptions - Masoumeh Pourrajab, Roya Roustaee, Ramli Bin Basri, Baharak Talebloo, Sara Kasmaienezhadfard (Journal of Educational, Health and Community Psychology, 2015)
AbstractThe aim of this study is to determine the relationship between adding value; trust and teacher satisfaction amongÂ primaryand secondary school teachers in Malaysia.In this research,375 teachers were selected based on conveniencerandom sampling from teachers who study in educational field. This study is quantitative research and data wereÂ collected based on questionnaire and were analyzed using descriptive, correlation and regression analysis. Based onPearson Product-Moment Correlation Coefficient the results show that the high significant relationship exists betweenÂ trust and teacher job satisfaction. However, low and negative relationship was found to exist between adding value andÂ teacherâs satisfaction. Regarding to multiple regression, there are significant contribution of trust and teacherÂ satisfaction. However, just adding value was not increase teacherjob satisfaction.Key words: Adding value âJob Satisfaction -Trust -Primary school- Teachers-Malaysia